An investigation into the performance of smallholder irrigation schemes in Limpopo Province, South Africa: success factors, typologies and implications for development - Denison, Jonathan Anthony Noel (Rhodes University, Faculty of Science, Department of Geography, 2019)
The research aimed to determine the factors that contribute to the success or failure of smallholder irrigation schemes in the Limpopo Province. It focussed on public-schemes where farmers share the water system Limpopo Province has more than half of the smallholder irrigation schemes in the country with an equipped area of approximately 28 000 ha. The main aims of the research were to identify key factors that explain performance and to develop a contemporary irrigation scheme typology. The research intended to provide a better perspective on how to focus investments across the multiple thematic areas that are associated with sustained and profitable irrigation farming activity. A survey of 102 irrigation schemes was conducted, comprising 82% of the population of schemes greater than 20 ha in Limpopo Province. The quantitative survey complemented prior in-depth qualitative research undertaken on Limpopo schemes. Data was consolidated into five performance indicators and 13 characteristic factors that impact performance. Schemes were viewed as technical and socio-biological systems where performance was determined by the dynamic interaction of multiple factors. The analysis was done in a complex systems framework using correlation, cluster and principle component analysis. It was postulated that over-arching concepts of productivity, profitability and manageability would explain why schemes succeed or fail. The schemes were found to be relatively very small in size with three quarters (74.8%) of them falling in the 50 to 250 ha size range, and only 11 schemes larger than 250 ha. Average plot sizes were 1.34 ha with a wide range between 0.18 and 16.25 ha. There were 65 operational schemes (equivalent to 63.7%), and 37 had failed (equivalent to 36.3%). Using a criterion for success of greater than 50% cropping intensity (to align with other studies and below which schemes can be considered to have failed), the success rate of the Limpopo schemes was 58%. The result was similar to the rest of South Africa and the same as the average rate for SADC identified in other studies using the same criterion. The schemes exhibited a mixed production purpose on average, with a significant market emphasis indicating these schemes have largely evolved from 'food schemes' to partly market-farming. Main crops grown were summer-maize and winter fresh-vegetables and cropping intensities on operational schemes ranged widely from 10% to 175%, with an average of 94%. Failure was associated with three dominant factors: energy type; infrastructure condition; and water resource constraints. The first two factors showed that manageability of technology was important. There is strong empirical evidence that pumped smallholder schemes are vulnerable in their physical form, prone to functional and financial failure, live much shorter lives, and perform no better than gravity-canal schemes. Out of the 37 schemes that failed, 34 (91.8%) were pumped. Pumped schemes tend to collapse suddenly while young and exhibit lower cut-off thresholds in productivity that, when crossed, trigger collapse. They also have much lower resilience to factors such as water stress or low farm-profitability. Pumped schemes need higher levels farm sophistication, market-oriented farming, and operational capability to keep the pumping pressure up. Water resource constraints were widespread, considerably more so on gravity schemes. Commercialising farmers were inhibited by lack of access to knowledge. Success was associated with numerous factors, but two findings stand out; the performance of gravity systems and the prevalence of land-exchange activity; the latter enabled by institutional flexibility and reflecting a process of 'bricolage' at play. Increased plot size was associated with increased commercialisation and, when larger than 1.8 ha, only commercialised farming was pursued. Market proximity seemed to play a role in increased longevity and to market access in commercialisation. These findings highlighted the importance of productivity and profitability in explaining success. Gravity schemes performed much more strongly in terms of longevity (nearly four times longer-lived) and similarly to pumped schemes in terms of cropping intensity. This was achieved under much greater water stress and with considerably worse infrastructure condition. Water efficiency was determined to be high on half of the schemes that were using short-furrow irrigation; equivalent, in a basin perspective, to drip irrigation. Two of the three top performing schemes (>150% intensity) were old gravity schemes. Farmers on approximately 75% of Limpopo smallholder schemes are currently engaging in land exchange transactions in a highly insecure and un-formalised institutional setup. Land exchange prevalence longer than two years was moderately associated with cropping intensity and strongly associated with commercialisation. This result has three important implications. First, it suggests that more land is utilised on the schemes when there is vibrant land-leasing activity. Secondly, schemes with a higher prevalence of long-term leasing seem to have a strong tendency to be more commercialised. Thirdly, the duration of the lease is significant, as neither single-season, nor annual leases yielded any positive associations, while those exchanges that were two years or longer, were associated with increased performance. These findings highlight the potential for longer-term land-exchange interventions to address the widespread low land utilisation on smallholder schemes, and to catalyse more commercially-oriented farming. An irrigation scheme typology was derived from the cluster analysis and was aligned to a contemporary irrigation farming typology. The key descriptors included technology type, purpose of farming and scheme management type. By matching scheme type to the farmer typology (or typologies), strategic decisions regarding technology choices for infrastructure, land, and water institutional interventions can be better informed. All schemes demand attention to the multiple factors required to achieve performance, not least water-tenure security, irrigation management organisational development, and infrastructure modernisation. Complexity was demonstrated by the finding that multiple factors contribute to success, and that there are many dimensions that change independently and have a cascading effect through the system in ways that are difficult to predict. Agricultural systems support to achieve productivity and profitability are essential for success. The research findings lead to the recommendation that, in addition, strategic planners must also consider the implications of the dominant factors of water-technology choices so that these are manageable, and the dynamics of farm-size change based on land exchange processes, in order to harness new opportunities to maximise irrigation scheme performance in future.
Keywords: Irrigation projects -- South Africa -- Limpopo; Farms, Small -- South Africa -- Limpopo; Land use -- South Africa -- Limpopo; Water-supply -- South Africa -- Limpopo